Development of Small-molecule HIV Entry Inhibitors Specifically Targeting gp120 or gp41 - Lu, Lu; Yu, Fei; Cai, Lifeng; K. Debnath, Asim; Jiang, Shibo (Current Topics in Medicinal Chemistry, 2016)
Human immunodeficiency virus type 1 (HIV-1) envelope (Env) glycoprotein surface subunit gp120 and transmembrane subunit gp41 play important roles in HIV-1 entry, thus serving as key targets for the development of HIV-1 entry inhibitors. T20 peptide (enfuvirtide) is the first U.S. FDA-approved HIV entry inhibitor; however, its clinical application is limited by the lack of oral availability. Here, we have described the structure and function of the HIV-1 gp120 and gp41 subunits and reviewed advancements in the development of small-molecule HIV entry inhibitors specifically targeting these two Env glycoproteins. We then compared the advantages and disadvantages of different categories of HIV entry inhibitor candidates and further predicted the future trend of HIV entry inhibitor development.
Keywords: Entry Inhibitor